Fatty liver syndrome associated with some post parturation period diseases - Veysi Aslan; Reşat Aştı; Mehmet Nizamlıoğlu; Tevfik Tekeli; Abdullah Başoğlu; Ülker Demirci (Eurasian Journal of Veterinary Sciences)
In this study, a total of 43 heads of cow were used. Some diseases and disorders such as retained placenta, ketosis, metritis, mastitis, hypocalcemia, indigestion and abomasal displacement were diagnosed in these cows.